A ANALYSIS OF STUDENT'S PROBLEMS IN MASTERING VOCABULARY: A CASE STUDY AT SMPN 4 PANGALENGAN - Nurul Aribah Nurul; Virga Putra Darma; Lili Sururi Asipi (Tomorrow's Education Journal, 2024)
This study aims to determine students' problems in vocabulary mastery. In this study, researchers investigated students' problems in vocabulary mastery at SMPN 4 Pangalengan. This study applies a descriptive method that uses qualitative analysis of research data. Researchers collect data that supports this study by conducting interviews, questionnaires, and observations. Participants in this study were 7th grade students, there were seven students as subjects in this study.The results of this study obtained that students' problems in vocabulary mastery were lack of student interest and motivation. There are two factors that cause lack of student interest and motivation (1) students' difficulty in memorizing vocabulary, (2) because of the use of smartphones which is the main factor in this problem.